Astolides A and B, antifungal and cytotoxic naphthoquinone-derived polyol macrolactones from Streptomyces hygroscopicus. Issue 52 (27th December 2018) - Alferova, Vera A.; Novikov, Roman A.; Bychkova, Olga P.; Rogozhin, Eugene A.; Shuvalov, Maxim V.; Prokhorenko, Igor A.; Sadykova, Vera S.; Kulko, Alexander B.; Dezhenkova, Lyubov G.; Stepashkina, Elena A.; Efremov, Mikhail A.; Sineva, Olga N.; et al.
Abstract: Two new natural compounds, astolides A, B, were isolated from Streptomyces hygroscopicus collected from the alkaline soil obtained from Saratov region, Russia. The structures were elucidated by interpretation of UV spectroscopic, MS, 1D and 2D NMR data. The relative configurations were determined by analysis of NOESY/ROESY spectra and coupling constants. The isolated compounds were evaluated for their inhibitory activity against bacteria, fungi and yeasts and showed pronounced antifungal activity. Both compounds are noticeably cytotoxic, being active against doxorubicin-resistant human leukemia cell line. Graphical abstract: Two new natural products astolides A, B from Streptomyces hygroscopicus show pronounced antifungal and cytotoxic activity.